Pengaruh Psikologi Gestalt dalam Mengantisipasi Miskonsepsi Matematika - Aliya Fitrahani (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This article discusses the importance of understanding concepts in the learning process whose peak can anticipate the occurrence of misconceptions in mathematics. The purpose of this study is to link mathematics learning with the psychological condition of students. Gestalt psychology says that learning is not just accumulating knowledge, but learning is a process of interaction between the individual and his environment. The research method uses a literature study by raising issues from Gestalt Psychology about meaning, understanding, and insight. The results of this study indicate that through the ability of insight, students are expected to be able to relate learning to everyday life, especially in Mathematics subjects where at the peak students are able to solve mathematical problems by understanding their own concepts, which in turn can anticipate all forms of misconceptions in mathematics.